External Balance And Budget In Malaysia - Wong , Hock Tsen (Asian Academy of Management (AAM), 2014)
This study examines external balance and budget in Malaysia. The unit root test results show that the variables examined are a mixture of stationary and non-stationary variables. The bounds testing results show that there is a long-run relationship between external balance and its determinants, including budget, and also between budget and its determinants, including external balance. Moreover, the results of the causality analysis show that the current account targeting hypothesis and the Ricardian equivalence hypothesis dominate the relationship between external balance and budget. Short-run and long-run measures are needed to address external imbalances. A healthy external balance is important for sustainable economic growth.